(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction Motivating children, not only for their personal advancement but also for the betterment of their families, with the support of parents, siblings, relatives, teachers, and classmates, was considered crucial in fostering children’s socio-emotional development. This research investigated the socio-emotional development of intermediate learners at Union Christian College. Method Employing a descriptive-correlational research design, the study sought to uncover the intricate connections between different factors influencing these learners’ socio-emotional growth. To accomplish this, participants responded to a survey questionnaire adapted for this study, assessing their socio-emotional development. The survey was administered through a Google Form to ensure efficient data collection. The researchers diligently adhered to ethical research protocols throughout the process, prioritizing responsible conduct in their work. Subsequently, the gathered data were subjected to comprehensive analysis using both descriptive and inferential statistical techniques. Results The outcomes revealed that the respondents exhibited high academic socio-emotional intelligence. Their relationships with fathers, mothers, siblings, and other relatives were rated outstanding, while their interactions with teachers and classmates were very good. Regarding the significance of these relationships, the connections forged with teachers and classmates emerged as significant contributors to the respondents’ academic socio-emotional development. However, it was noted that the profile variables of the respondents and their familial relationships did not significantly account for their academic socio-emotional development. Interpreting the findings, the researchers concluded that within the school context, the roles played by teachers and classmates were instrumental in fostering outstanding academic socio-emotional development among the respondents. Consequently, the study strongly recommended enhancing academic development programs that encourage dynamic teacher-learner and learner-to-learner engagements. Such programs were believed to play a pivotal role in propelling learners’ academic and socio-emotional development growth. Conclusion The research underscored the significance of motivating children through collaborative efforts of family, educators, and peers to nurture their socio-emotional development. Teachers and classmates were particularly influential in promoting this development within the school environment. In light of these insights, the study advocated for the augmentation of academic programs aimed at fostering productive interactions between teachers and learners and among peers. This approach was seen as essential for furthering the growth of learners in their journey toward achieving exceptional academic and socio-emotional development.